A positive feedback loop drives centrosome maturation in flies - Alvarez Rodrigo, I; Conduit, P; Baumbach, J; Novak, Z; Aydogan, M; Wainman, A; Raff, J (ColdSpring Habor Laboratory, 2018)
Centrosomes are formed when mother centrioles recruit pericentriolar material (PCM) around themselves. The PCM expands dramatically as cells prepare to enter mitosis (a process termed centrosome maturation), but it is unclear how this expansion is achieved. In flies, Spd-2 and Cnn form an extensive scaffold around the mother centriole that recruits other components of the mitotic PCM, and the Polo-dependent phosphorylation of Cnn at the centrosome is crucial for scaffold assembly. Here we show that, like Cnn, Spd-2 is specifically phosphorylated at centrosomes. This phosphorylation appears to create multiple phosphorylated S-S/T(p) motifs that allow Spd-2 to recruit Polo to the expanding scaffold. If Spd-2 cannot recruit Polo to the expanding scaffold, the scaffold is initially assembled around the mother centriole, but it cannot expand outwards, and centrosome maturation fails. We conclude that Spd-2, Polo and Cnn cooperate to form a positive feedback loop that drives the dramatic expansion of the mitotic centrosome in flies.